Mainstreaming of Gender Equality in Islamic Family Law: Opportunities and Challenges - Rahmawati, St. (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
This study discusses the mainstreaming of gender equality in Islamic family law. As it is known, gender equality and Islamic law have axiological links in realizing family household that practices the universal values such as justice, literature, peace, love, compassion, etc. This research is a qualitative study with a gender perspective linked to Islamic law. The discussion showed that a number of opportunities were found as normatively affirmed in the Qur'an which has the same spirit as the mainstreaming of gender equality in Islamic family law. Likewise, legal rules such as the Compilation of Islamic Law and the development of Islamic studies caused the normative theological understanding to support gender equality. However, it cannot be denied that the understanding of theological texts has begun to erode in the context of the implementation of Islamic family law. For the challenges, there were several aspects that hinder the mainstreaming of gender equality in Islamic family law, namely marginalization of women, community stereotypes against women, subordination of women, double burden on women, and violence against women.